THE Development of Hybrid Audiovisual E-book with Local Wisdom-Based Real-World Problems in Ngada’s Wela Maka - Fransiskus Xaverius Dolo; Maria Yuliana Kuai (International Journal of Instructions and Language Studies, 2023)
The imperative drives this research for educators to access high-quality online learning materials that facilitate practical, enjoyable, and contextually relevant Physics instruction. The primary objectives of this study are twofold: firstly, to develop a product in the form of an audiovisual e-book employing a hybrid model and integrating real-world problems for Physics instruction, drawing inspiration from the local wisdom Wela Maka of the Ngada community. Secondly, the research aims to assess the product's viability through validation by subject matter experts, media experts, instructional design experts, and language experts. Additionally, the study involves product testing with prospective users. The research adopts a Research & Development approach, utilizing the ADDIE model developed by Dick & Carey. The research cohort comprises five teachers and 34 high school students from Citra Bakti. Data collection methods encompass validation sheets and questionnaires, employing instruments such as validation assessment sheets and user response questionnaires. Data analysis involves both descriptive and inferential statistics. The research findings indicate that the average validation scores provided by subject matter experts, media experts, instructional design experts, and language experts are 4.60, 4.50, 4.35, and 4.48, respectively—all falling within the 'very good' category. Furthermore, the average product testing scores for both teachers and students are 4.49 and 4.54, respectively, also categorized as 'very good.' Based on this comprehensive data, it can be concluded that the audiovisual e-book hybrid model product is deemed suitable for integration into online learning platforms.